Multidimensional assessment of meat quality across anatomical regions of Kazakh horses: an integrative evaluation of meat quality traits, amino acid profiles, and fatty acid composition - Li, Luling; Ren, Wanlu; Wang, Ran; Li, Zexu; Ma, Shikun; Huang, Qiuping; Su, Yi; Shan, Dehaxi; Wang, Jianwen (Frontiers in Animal Science, 2025)
This study employed HE staining, LC-MS/MS, and related analytical techniques to assess meat quality, muscle fiber characteristics, and nutritional composition in five anatomical regions—longissimus dorsi (LD), diaphragm (DI), psoas major (PM), biceps femoris (BF), and semitendinosus (ST)—of the Kazakh horse. L* values in LD and PM were significantly elevated compared to the other regions (P < 0.01), whereas DI exhibited the highest a* value (P < 0.01). pH measurements indicated significantly higher values in LD, PM, BF, and ST relative to DI (P < 0.01). PM demonstrated superior tenderness, markedly surpassing that of BF. BF displayed the greatest cross-sectional area and diameter compared to other regions (P < 0.01). PM also presented significantly elevated essential amino acid (EAA)/non-essential amino acid (NEAA) and EAA/total amino acid (TAA) ratios (P < 0.01). ST contained the highest levels of total polyunsaturated fatty acids (PUFA) and exhibited the most significant n-6/n-3 PUFA ratio (P < 0.01). The observed intermuscular variation in physicochemical and nutritional properties provides a systematic foundation for quality stratification, targeted nutritional utilization, and processing optimization of Kazakh horse meat.